The Effects of Measurement Distance on the Broadside Symmetric Leaky Wave Antenna - Sutinjo, Adrian; Okoniewski, M.; Johnston, R. (Institute of Electrical and Electronics Engineers, 2008)
The effects of measuring a symmetric broadside leakywave antenna (LWA) at finite distances are examined. In particular,the broadside beam behavior near the beam splitting conditionis studied since the directivity error can be significant. The patternsat various distances, including the rule of thumb distance of?? ?? , are calculated and compared to the far-field (FF) pattern.In addition, variations in measurement error at the finite distancesdue to the sign of the leaky wave phase constant are identified.